Espriu parla en anglès. - KAUFMAN, ANDREW; CORTIJO OCAÑA, ANTONIO (Scripta)
The article focuses on the work of the Catalan poet Salvador Espriu and his limited availability in English, despite his recognition by literary critics. A brief sample of his poetry is presented, along with the English translation of three of his poetry collections: "Cementiri de Sinera," "Les Hores," and "Mrs. Death." The authors of the article highlight Espriu's importance in Catalan literature and compare him to other great poets, such as Lorca and Neruda, emphasizing the beauty and depth of his work. The translation aims to maintain fidelity to the original Catalan, reflecting its poetic essence in English.